Серьги из Светловодского могильника - Могилов, А.Д. (Археологія і давня історія України, 2020)
Статья посвящена рассмотрению серег из Светловодского могильника скифского времени, расположенного на юге Днепровской Правобережной Лесостепи. Scythian tribes and their North Pontic neighbors had
a magnificent set of jewelry in their everyday life: beads,
bracelets, appliques for costume decoration, rings, earrings,
torques, pins.
One of these categories, the earrings, is widely represented
in the large Svitlovodsk cemetery on the south of
the Dnieper Right Bank Forest-Steppe. During the 1975—
1990 by archaeological expeditions under the direction
of N. M. Bokiy and I. A. Kozyr more than 160 graves of
Scythian Age have been excavated.
A total of 45 items were found in 34 graves (21 % of
the total). They are ring-shaped and sometimes decorated
with beads or pendants. More often, the earrings have
been put into female burials. Sometimes one earring has
been occurred in the graves of male warriors.
The ring-shaped earrings are made of bronze wire. One
end is usually sharpened. This is the most numerous group
including 19 items (42 % of the total) from 16 burials.
Twisted wire hoop earrings (5 items, making up 11 % of
all earrings, come from 4 burials). Moreover, 3 items are
silver, 2 are bronze. They have been found jnly in female
tombs.
Hoop earrings with curved ends. 4 specimens (almost 9% of
earrings) have been found in two graves with buried women.
Ring-shaped smooth earrings with beads are the second
largest type in Svitlovodsk, including 11 items (24 %
of earrings from 11 graves). The body is usually bronze,
only once it is silver. The beads made of glass, less often of
copper, bone, bronze. Usually one bead was set onto body.
In several cases 2, 3 and 4 such decorations have been recorded.
This type is the most frequent attribute of female
burials, sometimes of a child and a teenager, in one case of
a wealthy male warrior.
Hoop earrings with twisted body and bead. Two specimens
(over 4% of earrings) come from 2 assemblages.
They are made of bronze and electrum.
Bronze hoop earrings with pendants. Two items (4 % of
earrings) come from two graves. In one case the pendant
was made of the animal tooth, in the second it was the
bronze ring.
Earrings in the shape of a stylized duck. Two copies
(4 % of earrings) were found in graves 70 and 77. In Svitlovodsk,
these jewelry were found in graves belonging to
poor community members.This category of jewelry from
Svitlovodsk shows the part of the set of jewelry of the common
population of Scythia. Скіфські племена та їх північнопричорноморські
сусіди використовували яскравий набір прикрас: намисто,
браслети, пластини для декору одягу, кільця,
сережки, гривни, шпильки.
Одна з таких категорій — сережки добре представлена
в великому могильнику біля м. Світловодськ на
півдні Дніпровського Лісостепового Правобережжя.
Протягом 1975—1990 рр. археологічними експедиціями
під керівництвом Н. М. Б окій та І. А. Козир там
було розкопано понад 160 поховань скіфського часу.
Більшість комплексів — ґрунтові. Втім, досліджено й
декілька курганів.
У 34 могилах Світловодського некрополя (21 % всіх поховань)
було знайдено 45 сережок. Вони кільчасті, з прямого,
чи, рідше, витого дроту, й іноді прикрашені намистинами
чи привісками. Частіше ці оздоби супроводжували
жінок. Інколи одна сережка була з чоловіком-воїном. У
статті проведена типологічна атрибуція та хронологічна
характеристика даного різновиду прикрас.
Сережки зі Світловодська, ілюструють нам частину
убору рядового населення Скіфії.